The Effect of the Problem-Based Learning Model on Mathematical Communication Skills and Learning Motivation of Eighth-Grade Students at MTs Negeri 2 Medan - Pakpahan, Aida Fitri Harun; Surya, Edy; Khairani, Nerli (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
The purpose of this study is to determine: (1) Whether there is an effect of the Problem-Based Learning model on students' mathematical communication skills. (2) Whether there is an interaction between the Problem-Based Learning model and students' initial mathematical ability (KAM) on their mathematical communication skills. (3) Whether there is an effect of the Problem-Based Learning model on students' learning motivation. (4) Whether there is an interaction between the Problem-Based Learning model and students' initial mathematical ability (KAM) on their learning motivation. This study is a quasi-experimental design. The population in this study was all students at MTs Negeri 2 Medan. Then, two classes were randomly selected, class VIII-D (30 students) and class VIII-E (30 students). The experimental class was given the Problem-Based Learning model treatment, and the control class was given the usual learning treatment. The instruments used consisted of: (1) a mathematical communication ability test, and (2) a student learning motivation questionnaire. These instruments were found to meet validity requirements, as well as reliability coefficients for mathematical communication ability and the learning motivation questionnaire. Data analysis was conducted using a two-way ANOVA. The results of the study indicate that (1) There is an effect of the Problem-Based Learning model on students' mathematical communication ability. (2) There is an interaction between the learning model and initial mathematical ability on students' mathematical communication skills. (3) There is an effect of the Problem-Based Learning model on students' learning motivation. (4) There is an interaction between the learning model and initial mathematical ability on students' learning motivation.